'The Journal' - Birmingham Trades Council, October 1961 (1961)
1961 1960-2000 "'The Journal' - Birmingham Trades Council, October 1961" [T0423.jpg], 1961, Birmingham Trades Council The Main article on the front page of the October 1961 issue of 'The Journal', published by the Birmingham Trades Council, concerns racial discrimination against black workers in the West Midlands. Several firms were operating a colour bar and the article looks at the role of employment exchanges. Another article condemns nuclear weapons tests.